A Novel Neutral Point Clamped Full-Bridge Topology for Transformerless Photovoltaic Grid-Connected Inverters - Pakdel, M.; Jalilzadeh, S. (Engineering, Technology & Applied Science Research, 2017)
This paper presents a novel neutral point clamped full-bridge topology for transformerless photovoltaic grid-tied inverters. Transformerless grid-connected inverters have been used widely in recent years since they offer higher efficiency and lower costs. Ground leakage current suppression is the main issue which should be considered carefully in transformerless photovoltaic grid-connected inverters. Among different methods used to decline ground leakage current, neutral point clamped (NPC) topologies are considered more useful and effective. In NPC topologies, the short-circuited output voltage at the freewheeling period is clamped to the middle of the DC bus voltage. Therefore, the common-mode voltage (CM) will be constant at the whole switching period. Various NPC topologies such as H6 [1], HB-ZVR [2], oH5 [3], and PN-NPC [4] have been proposed. In this paper, a novel NPC topology is proposed which has lower power losses and higher efficiency over previous topologies. Furthermore, the proposed NPC topology exhibits a similar ground leakage current with the PN-NPC topology. The proposed NPC topology is analyzed theoretically using simulation studies and an experimental prototype is provided to verify theoretical analysis and simulation studies.